Preparation method and application of magnetic nano adsorption material for targeted trapping of rare earth ions
By combining CM-β-CD with magnetic biochar material, CM-β-CD@RHMBC adsorption material was prepared, which solved the problem of low selectivity of traditional materials and achieved efficient effect of targeted capture of rare earth elements.
Patent Information
- Application Number
- CN202510112786.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional magnetic biochar adsorbent materials have low selectivity and are unable to target capture of rare earth elements.
Through esterification-polycondensation reaction, carboxymethyl-β-cyclodextrin (CM-β-CD) is combined with magnetic biochar material to prepare CM-β-CD@RHMBC adsorption material to achieve the function of targeting the capture of rare earth elements.
It improves the selectivity of adsorbent materials, can efficiently capture and recover low concentrations of rare earth ions from aqueous solutions, and reduces environmental pollution and resource waste.
Smart Images

Figure CN119897070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic nano-adsorption materials, and in particular to a preparation method and application of a magnetic nano-adsorption material for targeted capture of rare earth ions. Background Art
[0002] Rare earth elements include 15 lanthanide elements with atomic numbers from 57 to 71 in the periodic table, including lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu), as well as scandium (Sc) and yttrium (Y) with similar chemical properties, a total of 17 elements. Rare earth elements have unique physical and chemical properties and have become an indispensable strategic resource for the development of high-tech, cutting-edge defense technology and the transformation of traditional industries. In the process of rare earth production and separation and purification, a large amount of wastewater containing low-concentration rare earth ions will be generated. If it is directly discharged, it will not only cause serious waste of rare earth resources, but also bring serious environmental pollution and pose irreversible harm to human health and production and life.
[0003] Among many technologies, the adsorption method is favored because of its simple operation, low cost and high efficiency. However, traditional adsorption materials often have problems such as low selectivity, poor adsorption effect, slow adsorption rate, small processing volume and difficult recovery. In particular, the adsorption selectivity is low, resulting in a high impurity content in the separated and recovered rare earth materials, and the obtained products cannot be directly used. Therefore, improving the selection of adsorption materials is the most critical. Biochar not only has the advantages of large specific surface area, developed pores and low cost, but also can make full use of waste biomass and improve resource recycling rate. However, since biochar is difficult to separate and recover from aqueous solution after adsorbing metal ions, scientific researchers often combine biochar with magnetic materials to improve its recovery efficiency, which has become a hot spot in the field of adsorption material research. In the prior art, CN202410822864.5 discloses a magnetic tea residue biochar adsorbent and its preparation method and application, which can be used for adsorbing aflatoxin. CN202410903735.9 discloses a method for preparing a modified magnetic biochar adsorption material, which can be used for adsorbing Cr(VI). However, the above-mentioned magnetic biochar adsorption material still lacks certain selectivity.
[0004] As a cyclic oligosaccharide, β-CD has a hydrophilic outer edge and an internal hydrophobic cavity structure. It has a large number of primary hydroxyl groups on the outer edge that can chelate metal ions and many secondary hydroxyl groups on the inner ring. Its outer hydroxyl groups and "molecular recognition" cavity can selectively remove metal ions through host-guest interactions. However, due to its single functional group and the fact that the monomer is easily hydrolyzed, its application in the field of water treatment is limited. In addition, its nanoparticles are difficult to recover when dispersed in aqueous solution, resulting in resource waste and secondary pollution. To solve these problems, researchers first chemically modified some hydroxyl groups into other specific functional groups to enhance the adsorption capacity of metal ions, and then coupled it with magnetic technology based on the chemical modification. Carboxymethyl-β-cyclodextrin (CM-β-CD) is a compound formed by connecting a carboxymethyl group to the cyclodextrin cavity through an ether bond. The carboxyl group of CM-β-CD can dissociate into COO in a weakly acidic or alkaline environment. - , can form complexes with metal ions, enhance the electrostatic interaction with other metal ions, and thus improve the adsorption capacity of metal ions. However, it is easily soluble in water and has poor stability. Therefore, grafting CM-β-CD onto Fe3O4-based magnetic nanomaterials can not only improve the stability of CM-β-CD materials, but also make the adsorbent have the ability to selectively identify the encapsulated metal ions, and at the same time have good magnetic separation and recovery performance. Badruddoza et al. modified CM-β-CD onto the surface of Fe3O4 particles by the carbodiimide method and prepared CM-β-CD-modified Fe3O4 nanoparticles (CMCD-MNPs) for the removal of Cu in aqueous solution. 2+ Badruddoza et al. further used CM-β-CD polymer-modified Fe3O4 magnetic nanoparticles (CMPCD-MNPs) to remove bisphenol A (BPA) and Pb from aqueous solutions. 2+ ions. Cui Can et al. prepared raw biochar using palm fiber as raw material, and then successfully prepared β-cyclodextrin-modified magnetic biochar (β-CD@PFMBC) by chemical coprecipitation, and used it as an adsorbent to effectively remove Pb(II) from aqueous solution. Huang et al. synthesized a β-cyclodextrin-chitosan modified walnut shell biochar (β-CCWB) for efficient removal of Cr(VI). However, the above technologies rarely use CM-β-CD composite magnetic biochar adsorption materials to adsorb and remove low concentrations of rare earth ions in wastewater. Summary of the invention
[0005] The technical problem to be solved by the present invention is that magnetic biochar is composed of biochar and magnetic medium, which can not only solve the problem of biochar recycling, but also can be used for the adsorption of valuable metal ions. However, its selectivity is low and it cannot achieve targeted capture of metal elements.
[0006] To solve the above problems, the present invention uses carboxymethyl-β-cyclodextrin and uses esterification-polycondensation reaction to compound it with magnetic biochar material to obtain a magnetic biochar material that can target and capture rare earth elements. The preparation method uses a one-pot hot method, which is simple to operate and can be completed in one reactor without step-by-step. The reaction conditions are also relatively simple and do not require too many chemical reagents, which is convenient for large-scale promotion and use.
[0007] To achieve the above object, the present invention is mainly achieved by the following technical means: a method for preparing a CM-β-CD@RHMBC adsorption material, comprising the following steps:
[0008] (1) Preparation of biochar - RHBC: The biomass is washed, dried, crushed and then sieved; the sieved powder is calcined at high temperature, cooled and collected to obtain biochar - RHBC;
[0009] (2) Preparation of alkaline biochar - alkaline RHBC: Add the biochar prepared in step (1) to the alkaline solution to obtain a mixed solution 1; filter out the solid particles in the mixed solution 1 after stirring, wash with water to remove impurities, and then dry the obtained solid particles to obtain alkaline biochar - alkaline RHBC, and the remaining alkaline solution is recycled; the alkaline solution can remove metal oxides and incompletely pyrolyzed organic matter on the surface of biochar, while increasing the negative charge on its surface, which helps to adsorb positively charged metal ions. Secondly, alkaline modification can provide more oxygen-containing functional groups on the surface of biochar and promote the development of pore structure, thereby improving its adsorption performance.
[0010] (3) Preparation of carboxymethyl-β-cyclodextrin modified magnetic biochar - CM-β-CD@RHMBC: Add the alkaline RHBC prepared in step (2) to the carboxymethyl-β-cyclodextrin solution at 55-90°C to obtain a mixed solution 2; add FeCl3·6H2O and FeSO4·7H2O after mixing to obtain a mixed solution 3; heat the mixed solution 3 while stirring, and then quickly add NH3·H2O to the mixed solution 3 to obtain a mixed solution 4; after a period of reaction, add a surfactant to the mixed solution 4 to obtain a mixed solution 5, stir and react at a certain temperature, age after the reaction, filter, and wash the solid particles with anhydrous ethanol and deionized water, and dry to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar - CM-β-CD@RHMBC. CM-β-CD is grafted onto the alkaline biochar, and through an esterification-polycondensation reaction, the carboxyl group (-COOH) of CM-β-CD reacts with the hydroxyl group (-OH) on the surface of the biochar to form an ester bond. This step (forming ester bonds) not only increases the oxygen-containing functional groups on the biochar surface, but also introduces the special cavity structure of CM-β-CD, which improves the selective adsorption capacity of specific metal ions. Fe3O4 magnetic nanoparticles are introduced on the surface of biochar, and these nanoparticles can be evenly dispersed in the porous structure of biochar. This step makes the biochar magnetic, which facilitates rapid separation under the action of an external magnetic field. Adding surfactants, such as sodium dodecylbenzene sulfonate (SDBS), during the reaction process can further improve the dispersibility and stability of the material, prevent the agglomeration of nanoparticles, and maintain the porous structure of biochar.
[0011] Furthermore, the biomass in step (1) is one or a mixture of more than one of rice husk, rice straw, wheat straw, cotton straw, walnut shell, sawdust or corn straw.
[0012] Furthermore, in step (1), the biomass is placed at 50-80°C and dried for 5-24 hours, and the drying method is oven drying or vacuum drying; after crushing, it is sieved through a 60-150 mesh screen; the pyrolysis rate during calcination is between 5-15°C / min; the pyrolysis temperature is between 300-900°C; and the pyrolysis time is between 1-7 hours. As the heating rate increases, the biochar will gradually change from slow pyrolysis to fast pyrolysis, the volatile components of the raw materials will evaporate quickly, the specific surface area will increase, and pores will form quickly, so that the adsorption will achieve a better effect. As the pyrolysis temperature increases, the elemental composition and structure of the biochar change significantly, its polarity decreases, and its hydrophobicity increases; the porosity of the biochar increases, which is conducive to adsorption. A longer pyrolysis time can promote the formation and expansion of pores, especially mesopores and macropores. However, too long a pyrolysis time may cause the pore structure to become unstable. When the pyrolysis time exceeds a certain range, the unstable components in the biochar will decompose again, produce more ash and affect the yield of the biochar. Appropriate pyrolysis temperature and time can optimize the pore structure and surface functional groups of biochar, thereby improving the adsorption performance. Too high or too low pyrolysis temperature and time may lead to a decrease in the adsorption performance of biochar.
[0013] Further, in step (2), OH in the mixed solution 1 - The concentration is between 1 and 4 mol / L, and the mass of biochar is between 1 and 200 g / L; after stirring for a certain period of time, filter and wash the solid particles with deionized water to pH = 7 ± 0.5. Use a certain concentration of alkaline solution to fully activate the biochar. Too high a concentration will cause waste of resources and pollute the environment, and too low a concentration will not fully activate the biochar.
[0014] Furthermore, in step (2), the stirring rate of the mixed solution 1 is between 200 and 1200 r / min. -1 , the stirring time is between 1 and 24 hours; the solid particles obtained by filtration are placed at 50-80°C and dried for 5-24 hours, and the drying method is oven drying or vacuum drying. Appropriate stirring rate and time can ensure that the biochar is fully in contact with the solution and improve the activation efficiency. Too high a stirring rate and too long a stirring time will increase the cost and time, while too low a stirring rate and too short a stirring time will not fully activate the biochar.
[0015] Furthermore, in step (3), CM-β-CD and alkaline RHBC are added to deionized water to obtain a mixed solution 2, and the mass ratio of CM-β-CD to alkaline RHBC is 0.5 to 7. Within this range, it can ensure that CM-β-CD is effectively grafted on the alkaline RHBC to improve the adsorption performance. If it is too high, it will cause waste of CM-β-CD or cause clogging of biochar pores; if it is too low, it will lead to a decrease in the adsorption effect of the adsorbent. 3+ with Fe 2+ The molar ratio is between 1:2 and 2:1, Fe3+ and Fe 2+ It is the basic element that constitutes magnetic materials (such as Fe3O4). Different molar ratios will lead to different chemical compositions and crystal structures, thus affecting the magnetic properties of the material. For example, Fe3O4 is a spinel structure magnetic material, and its magnetic properties depend on Fe 3+ and Fe 2+ The ratio of Fe 3+ and Fe 2+ Different combinations of FeO can form different magnetic materials, such as Fe3O4, Fe2O3, etc., which have different magnetic susceptibility and coercivity. If the ratio is not correct, the desired magnetic material may not be formed, or other by-products may be formed. 3+ and Fe 2+ The ratio of Fe to Zn will also affect the adsorption performance of the material. Different magnetic materials have different surface functional groups and pore structures, which determine their adsorption capacity for specific substances. Different molar ratios may require different reaction conditions, such as temperature, pressure and reaction time. The correct molar ratio can ensure the smooth progress of the reaction and obtain the desired magnetic material. The molar ratio between 1:2 and 2:1 can ensure that Fe 3+ with Fe 2+ Fully react to generate Fe3O4 to avoid waste.
[0016] Further, in step (3), the mixed solution 2 is stirred at room temperature at a stirring rate of 800 to 1200 r min -1 , the stirring time is between 1 and 24 hours; the mixed solution 2 is heated to 55-90°C and FeCl3·6H2O and FeSO4·7H2O are added to obtain a mixed solution 3. Appropriate stirring rate and time can ensure that the biochar is fully in contact with the solution and improve the reaction efficiency. Too high a stirring rate and too long a stirring time will increase the cost and time, while too low a stirring rate and too short a stirring time will not allow the biochar to fully react. Appropriate temperature is conducive to the generation of magnetic particles by FeCl3·6H2O and FeSO4·7H2O. If the temperature is too low, the reaction will not proceed, and if the temperature is too high, energy will be wasted.
[0017] Furthermore, in step (3), the volume ratio of ammonia water to deionized water in the mixed solution 4 is between 1:2 and 1:7, and the solution temperature is maintained at 55 to 90°C for 25 to 90 minutes; the surfactant in the mixed solution 4 is one or more of sodium dodecylbenzene sulfonate (SDBS), dodecyltrimethylammonium bromide (DTAB), or sodium dodecyl sulfate (SDS), the concentration of the added surfactant is between 1 and 30 g / L, and the stirring temperature is 55 to 90°C. Appropriate NH3·H2O is conducive to the esterification-polycondensation reaction, too low a concentration will not cause the esterification-polycondensation reaction, and too high a concentration will cause a waste of energy. Appropriate temperature is conducive to the reaction, too low a temperature will cause the reaction to not proceed, and too high a temperature will cause a waste of energy.
[0018] Furthermore, the reaction time of step (3) is between 80-120 min; the aging time is between 5 and 60 min; the obtained solid particles are washed alternately with anhydrous ethanol and deionized water for 1 to 10 times; the constant temperature drying parameter is dried at 50 to 80°C for 5 to 24 hours. The aging time affects the stability of the adsorbent. Appropriate aging time helps to improve the stability of the adsorbent and maintain good performance during the adsorption process. Anhydrous ethanol and deionized water are used as washing solvents to effectively remove impurities on the surface of the adsorbent. Deionized water can remove ionic pollutants on the surface, while anhydrous ethanol can remove organic pollutants. This alternating washing method can ensure the cleanliness of the adsorbent surface and improve its purity and adsorption performance.
[0019] A magnetic material for targeted capture of valuable metal ions prepared by any of the above methods. The material is a carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@RHMBC), which is formed by esterification-polycondensation reaction of CM-β-CD, Fe3O4 and alkaline RHBC to form stable chemical bonds, thereby enhancing the structural stability and adsorption performance of the material. The biochar of the material has a porous structure, providing a large number of adsorption sites for rare earth ions. The carboxyl groups on CM-β-CD can form electrostatic effects with rare earth ions to enhance the adsorption capacity. CM-β-CD has a special cavity structure and a size similar to that of rare earth ions, and can form a package and effect with rare earth ions to achieve selective capture of rare earth ions. The coordination effect between CM-β-CD and metal ions enables the material to specifically identify and capture target metal ions. The introduction of Fe3O4 magnetic nanoparticles makes the material magnetic, and the material can be quickly aggregated under the action of an external magnetic field, making it easy to separate from the solution. Rare earth ions include 15 lanthanide ions, including lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu), as well as scandium (Sc) and yttrium (Y) with similar chemical properties, a total of 17 ions. The material has good adsorption properties for other rare earth ions. The material can effectively remove and recover valuable metal ions, such as rare earth and copper (Cu) from industrial wastewater. 2+ ), lead (Pb 2+ ), cadmium (Cd 2+ ), etc., which not only reduces environmental pollution but also realizes resource recycling. Since the material has the ability to capture specific metal ions in a targeted manner, it can efficiently recover valuable rare earths from rare earth ore processing wastewater, leaching tailings, and leaching liquid. The material can be used in the fields of wastewater treatment and purification of valuable metal ions.
[0020] The beneficial effects of the present invention are:
[0021] 1. The method is simple and low cost: The preparation method adopts a one-pot hot method, which is simple to operate and can be completed in one reactor without step-by-step. The reaction conditions are simple and the requirement for chemical reagents is small. It is easy to promote and use on a large scale, simplifies the preparation process and reduces costs.
[0022] 2. Treating waste with waste and recycling resources: A CM-β-CD@RHMBC adsorption material and its preparation method and application are provided. Waste biomass is used to make biochar materials to turn waste into treasure; carboxymethyl cyclodextrin is used to achieve targeted adsorption, and low-concentration rare earth ions in aqueous solution are selectively adsorbed, separated and recovered. The obtained rare earth products are of high purity, which not only effectively solves the problem of low-concentration rare earth ions in aqueous solution that are difficult to recover, protects the ecological environment, but also obtains high-purity rare earth products without secondary pollution, which is in line with my country's "carbon neutrality and carbon peak" development strategy. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the FTIR spectrum of CM-β-CD@RHMBC provided in Example 1 of the present application.
[0024] Figure 2 This is the XRD spectrum of CM-β-CD@RHMBC provided in Example 1 of the present application.
[0025] Figure 3 This is a diagram showing the effects of different adsorbents on rare earth erbium solution provided in Example 2 of the present application.
[0026] Figure 4 This is a diagram showing the effects of materials prepared under different conditions on the rare earth erbium solution provided in Example 3 of the present application.
[0027] Figure 5 This is a relationship diagram between the adsorption rate of CM-β-CD@CSMBC and the type of rare earth ions provided in Example 7 of the present application.
[0028] Figure 6 This is a relationship diagram of the concentration change of CM-β-CD@CSMBC provided in Example 8 of the present application after adsorption of coexisting metal cations at different concentrations.
[0029] Figure 7 This is a relationship diagram of the concentration change of CM-β-CD@CSMBC provided in Example 8 of the present application after adsorption of coexisting anions at different concentrations. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] All raw materials in the examples of the present invention, unless otherwise specified, are commercially available.
[0032] Embodiment 1:
[0033] A preparation method and application of a CM-β-CD@RHMBC adsorption material, comprising the following steps:
[0034] (1) The rice husk was washed three times with deionized water to remove dust and impurities, and then dried in an oven at 60°C. The husk was crushed with a wall-breaking machine and passed through a 100-mesh sieve. A certain amount of the sieved rice husk was put into a crucible and compacted, wrapped with tin foil, and placed in a muffle furnace. The husk was calcined at a pyrolysis temperature of 300°C for 4 h at a heating rate of 10°C / min, and then cooled to room temperature. After cooling, the husk was taken out and sealed in a transparent plastic bag to prevent moisture absorption, thereby obtaining rice husk biochar (RHBC).
[0035] (2) Add 2 g of rice husk biochar prepared in step 1) into 200 mL of 2 mol / L NaOH solution to obtain a mixed solution 1. Then, the mixed solution 1 was heated at 300 r min -1 After stirring for 2 hours, the solid particles in the mixed solution 1 were filtered out, and then washed with deionized water for multiple times until the pH value was 7±0.5. The obtained solid particles were then dried in a drying oven at a vacuum drying temperature of 80°C and a drying time of 17 hours to obtain alkaline rice husk biochar (alkaline RHBC).
[0036] (3) Dissolve 1.5 g of carboxymethyl-β-cyclodextrin (CM-β-CD) in 75 ml of deionized water at 55-90°C, and then add 2 g of alkaline RHBC prepared in step 2) to obtain a mixed solution 2, wherein the mass ratio of CM-β-CD to alkaline RHBC is 0.75. The mixed solution 2 is continuously stirred at room temperature at a stirring rate of 1200 r min -1 , stirring time is between 2h; then the mixed solution 2 is heated to 75℃, 2.36g FeCl3·6H2O and 1.62g FeSO4·7H2O are added respectively, Fe 3+ with Fe 2+ The molar ratio was between 3:2 to obtain mixed solution 3; then 15 ml of NH3·H2O was quickly added to the mixed solution 3, and the volume ratio of ammonia water to deionized water was between 1:5 to obtain mixed solution 4; the mixed solution 4 was reacted at 75°C for 25 min, and then 1.2 g of sodium dodecylbenzene sulfonate (SDBS) was added to the mixed solution 4 to obtain mixed solution 5, which was continuously stirred at 75°C for 100 min, aged for 0.5 h, and the solid particles obtained after filtration were washed 5 times with anhydrous ethanol and deionized water, and then dried at a constant temperature, and the vacuum drying temperature was between 80°C; dried for 17 h to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@RHMBC).
[0037] Verification results:
[0038] like Figure 1 As shown in Figure 2, RHBC, carboxymethyl-β-cyclodextrin and biochar modified materials are all at 3379 cm – 1 The broad peak at 2928 cm-1 is attributed to the OH stretching vibration. – 1 The stretching vibration peak at 1421 cm -1 The absorption peaks that appear are related to the bending vibration of CH and are at 947, 1024, 1164 and 1604 cm -1 The characteristic peaks of CM-β-CD can be observed at 947 cm -1 The characteristic absorption peaks at 1024 and 1164 cm-1 are the -1,4-skeleton vibrations of the D-pyranose structural unit in β-CD. -1 The absorption peaks at 1603 cm -1 The absorption peak of CM-β is related to the stretching vibration of C=O.
[0039] -CD@RHMBC showed absorption peaks related to CH and CO in CM-β-CD. In addition, a peak at 579 cm -1 The peak of Fe3O4 and CM-β-CD was attributed to the stretching vibration of Fe-O. The above results indicate that Fe3O4 and CM-β-CD were successfully modified onto biochar.
[0040] like Figure 2 As shown in the figure, the XRD spectrum of RHBC shows a broad graphene-like peak near 2θ=20.27°~23.92°, indicating that rice husk can be pyrolyzed to form biochar with a porous structure and belongs to amorphous carbon. CM-β-CD@RHMBC has obvious characteristic diffraction peaks at 2θ of 30.15°, 35.53°, 43.18°, 53.60°, 57.20° and 62.80°, and the corresponding crystal planes are (220), (311), (400), (422), (511) and (440), indicating that the generated nanoparticles have a spinel structure, indicating that Fe3O4 is successfully loaded on biochar, and the modification of the surface of magnetic nanoparticles with CM-β-CD does not lead to the structure of nanoparticles. However, CM-β–CD@RHMBC does not show the peaks related to CM-β-CD and RHBC. This may be because the crystal form of Fe3O4 is stronger than that of CM-β-CD and RHBC, which masks the peaks of CM-β-CD and RHBC.
[0041] Embodiment 2:
[0042] The embodiment of the present application provides an application of a CM-β-CD@RHMBC adsorption material; RHBC, Fe3O4, CM-β-CD, alkaline RHBC and CM-β-CD@RHMBC adsorption materials prepared in Example 1 are added to an aqueous solution containing rare earth Er(III); wherein the concentration of rare earth erbium in the aqueous solution is 20 mg / L, the amount of CM-β-CD@RHMBC adsorption material is 30 mg, the temperature of the aqueous solution is 298K, the stirring speed is 160 rpm, and the reaction time is 120 min.
[0043] like Figure 3 As shown in Figure 2, the adsorption effect of different adsorbents on rare earth ion solutions in aqueous solution. Figure 3 It can be seen that CM-β-CD@RHMBC has a better adsorption effect than the three unmodified adsorbents, which shows the feasibility of CM-β-CD@RHMBC materials. It can also be seen that the adsorption effect of alkaline RHBC is better than that of RHBC, which shows that alkaline RHBC is beneficial to Er 3+ adsorption.
[0044] Embodiment 3:
[0045] The embodiment of the present application provides an application of a CM-β-CD@RHMBC adsorption material; four types of CM-β-CD@RHMBC adsorption materials prepared by changing the conditions of adding ammonia water and heating in Example 1 are added to an aqueous solution containing rare earth Er(III); wherein the concentration of rare earth erbium in the aqueous solution is 100 mg / L, the amount of CM-β-CD@RHMBC adsorption material is 30 mg, the temperature of the aqueous solution is 298K, the stirring speed is 160 rpm, and the reaction time is 120 min.
[0046] like Figure 4 The results show that the materials prepared under different conditions have an effect on 10 mg / L Er 3+ The adsorption effect of the solution. Figure 4 It can be seen that the adsorption effect of (heating and adding ammonia water) is better than that of (not heating and adding ammonia water), and the adsorption time is shorter, indicating that the heating condition is conducive to the adsorption of Er by CM-β-CD@RHMBC 3+ Since alkaline RHBC and heating are both beneficial to the adsorption of Er 3+ In order to improve the adsorption of CM-β-CD, an adsorbent loaded with alkaline RHBC was prepared, and then an adsorption experiment was carried out. The saturated adsorption was basically achieved in 30 minutes, and the saturated adsorption amount was 84.46 mg / g.
[0047] Embodiment 4:
[0048] Rice straw or corn straw is used as biomass, and the rest is the same as in Example 1.
[0049] Example 5: (the order of addition during preparation is different)
[0050] A method for preparing a CM-β-CD@RSMBC adsorption material comprises the following steps:
[0051] (1) The rice straw was washed three times with deionized water to remove dust and impurities, and then dried in an oven at 60°C. It was crushed with a wall breaker and passed through a 100-mesh sieve. A certain amount of rice straw biochar was placed in a crucible, compacted, wrapped with tin foil, and placed in a muffle furnace. It was calcined at a heating rate of 10°C / min and a pyrolysis temperature of 500°C for 2 h, and finally cooled to room temperature. After cooling, it was taken out and collected and sealed in a transparent plastic bag to prevent moisture absorption, thereby obtaining rice straw biochar (RSBC).
[0052] (2) Add 2 g of the rice straw biochar prepared in step 1) into 200 mL of 2 mol / L NaOH solution to obtain a mixed solution 1. Then, the mixed solution 1 was heated at 300 r min. -1 After stirring for 2 hours, the solid particles in the mixed solution 1 were filtered out and washed with deionized water for several times to remove impurities until the pH value was 7±0.5. The obtained solid particles were then dried in a drying oven at a vacuum drying temperature of 80°C and a drying time of 17 hours to obtain alkaline rice straw biochar (alkaline RSBC).
[0053] (3) Dissolve 1.5 g of carboxymethyl-β-cyclodextrin (CM-β-CD) in 75 mL of deionized water at 55-90°C, then add 2.36 g of FeCl3·6H2O and 1.62 g of FeSO4·7H2O. 3+ with Fe 2+ The molar ratio was 3:2, and a mixed solution 2 was obtained. Then, 15 mL of NH3·H2O was quickly added to the mixed solution 2 to obtain a mixed solution 3, in which the volume ratio of ammonia water to deionized water was 1:5; the mixed solution 3 was continuously stirred at room temperature at a stirring rate of 1200 r min -1, stirring time is between 2h; then the mixed solution 3 is heated to 75℃, and then 2g of alkaline RSBC prepared in step (2) is added, the mass ratio of CM-β-CD to alkaline RSBC is 0.75, and a mixed solution 4 is obtained; then 10mL of NH3·H2O is quickly added to the mixed solution 4 to obtain a mixed solution 4, the mixed solution 4 is reacted at 75℃ for 25min, and then 1.2g of sodium dodecylbenzene sulfonate (SDBS) is added to the mixed solution 4 to obtain a mixed solution 5, which is continuously stirred at 75℃; after the reaction is completed, the mixed solution 5 is aged for 0.5h, and the solid particles obtained after filtration are washed with anhydrous ethanol and deionized water for multiple times, and then dried at a constant temperature, and the vacuum drying temperature is between 80℃; the drying time is between 17h to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@RSMBC).
[0054] Embodiment 6:
[0055] A method for preparing a CM-β-CD@CSMBC adsorption material comprises the following steps:
[0056] (1) The corn straw was washed three times with deionized water to remove dust and impurities, and then dried in an oven at 60°C. It was crushed with a wall breaker and passed through a 100-mesh sieve. A certain amount of rice straw biochar was placed in a crucible, compacted, wrapped with tin foil, and placed in a muffle furnace. It was calcined at a heating rate of 10°C / min and a pyrolysis temperature of 600°C for 2 h, and finally cooled to room temperature. After cooling, it was taken out and collected and sealed in a transparent plastic bag to prevent moisture absorption, thereby obtaining corn straw biochar (CSBC).
[0057] (2) Add 2 g of the corn straw biochar prepared in step 1) into 200 mL of 2 mol / L NaOH solution to obtain a mixed solution 1. Then, the mixed solution 1 was heated at 300 r min. -1 After stirring for 2 hours, the solid particles in the mixed solution 1 were filtered out and washed with deionized water for several times to remove impurities until the pH value was 7±0.5. The obtained solid particles were then dried in a drying oven at a vacuum drying temperature of 80°C and a drying time of 17 hours to obtain alkaline corn straw biochar (alkaline CSBC).
[0058] (3) Dissolve 1.5 g of carboxymethyl-β-cyclodextrin (CM-β-CD) in 75 mL of deionized water at 55-90°C, then add 2.36 g of FeCl3·6H2O and 1.62 g of FeSO4·7H2O. 3+ with Fe 2+The molar ratio was 3:2, and a mixed solution 2 was obtained. Then, 15 mL of NH3·H2O was quickly added to the mixed solution 2 to obtain a mixed solution 3, in which the volume ratio of ammonia water to deionized water was 1:5; the mixed solution 3 was continuously stirred at room temperature at a stirring rate of 1200 r min -1 , stirring time is between 2h; then the mixed solution 3 is heated to 75℃, and then 2g of alkaline CSBC prepared in step (2) is added, the mass ratio of CM-β-CD and alkaline RSBC is 0.75, and a mixed solution 4 is obtained; then 10mL of NH3·H2O is quickly added to the mixed solution 4 to obtain a mixed solution 4, the mixed solution 4 is reacted at 75℃ for 25min, and then 1.2g of sodium dodecylbenzene sulfonate (SDBS) is added to the mixed solution 4 to obtain a mixed solution 5, which is continuously stirred at 75℃; after the reaction is completed, the mixed solution 5 is aged for 0.5h, and the solid particles obtained after filtration are washed with anhydrous ethanol and deionized water for multiple times, and then dried at a constant temperature, and the vacuum drying temperature is between 80℃; the drying time is between 17h to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@CSMBC).
[0059] Embodiment 7:
[0060] The embodiment of the present application provides an application of a CM-β-CD@RHMBC adsorption material; the CM-β-CD@CSMBC adsorption material prepared in Example 6 is added to an aqueous solution containing rare earth Er(III); wherein the concentration of rare earth erbium in the aqueous solution is 10 mg / L, the amount of CM-β-CD@CSMBC adsorption material is 30 mg, the temperature of the aqueous solution is 298K, the stirring speed is 160 rpm, the reaction time is 120 min, and the types of rare earth ions are changed to lanthanum (La), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), dysprosium (Dy), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and yttrium (Y).
[0061] like Figure 5 As shown in the figure, the relationship between the adsorption rate of CM-β-CD@CSMBC and the type of rare earth ions is Figure 5 It can be seen that the CM-β-CD@CSMBC nanomagnetic material shows good selectivity for various rare earth ions, and the adsorption rate can basically reach more than 95%, which shows that the prepared nanomagnetic material has good selective adsorption ability for rare earth elements.
[0062] Embodiment 8:
[0063] The present application provides an application of a CM-β-CD@RHMBC adsorption material; the CM-β-CD@CSMBC adsorption material prepared in Example 6 is added to an aqueous solution containing rare earth Er(III); wherein the concentration of rare earth erbium in the aqueous solution is 10 mg / L, the amount of CM-β-CD@CSMBC adsorption material is 30 mg, the temperature of the aqueous solution is 298 K, the stirring speed is 160 rpm, the reaction time is 120 min, and the composition of the rare earth solution is changed, that is, 3, 10, and 15 mg / L of Mg are added to the solution containing erbium, respectively. 2+ , Ca 2+ 、Zn 2+ 、Ni 2+ 、Na + 、Al 3+ .
[0064] like Figure 6 The figure shows the relationship between the concentration changes of CM-β-CD@CSMBC after the adsorption of metal cations at different concentrations. Figure 6 It can be seen that CM-β-CD@CSMBC nanomagnetic material has a significant effect on Mg 2+ , Ca 2+ 、Zn 2+ 、Ni 2+ 、Na + 、Al 3+ The concentration of impurity ions did not change before and after adsorption, which also proved that CM-β-CD@CSMBC has good ability to selectively adsorb rare earths.
[0065] Embodiment 9:
[0066] The present application provides an application of a CM-β-CD@RHMBC adsorption material; the CM-β-CD@CSMBC adsorption material prepared in Example 6 is added to an aqueous solution containing rare earth Er(III); wherein the concentration of rare earth erbium in the aqueous solution is 10 mg / L, the amount of CM-β-CD@CSMBC adsorption material is 30 mg, the temperature of the aqueous solution is 298 K, the stirring speed is 160 rpm, the reaction time is 120 min, and the composition of the rare earth solution is changed, that is, 3, 10, and 15 mg / L of Cl are added to the solution containing erbium, respectively. - 、SO4 2- 、NO3 - 、CO3 2- PO4 3- .
[0067] like Figure 7 The graph shows the relationship between the concentration changes of CM-β-CD@CSMBC after the adsorption of anions at different concentrations. Figure 7It can be seen that the concentration of CM-β-CD@CSMBC nanomagnetic material in wastewater does not change before and after the adsorption of anions of various concentrations, which also proves that CM-β-CD@CSMBC has a good ability to selectively adsorb rare earths.
[0068] Embodiment 10:
[0069] A method for preparing a CM-β-CD@CSMBC adsorption material comprises the following steps:
[0070] (1) The corn straw was washed three times with deionized water to remove dust and impurities, and then dried in an oven at 60°C. It was crushed with a wall breaker and passed through a 100-mesh sieve. A certain amount of rice straw biochar was placed in a crucible, compacted, wrapped with tin foil, and placed in a muffle furnace. It was calcined at a heating rate of 10°C / min and a pyrolysis temperature of 600°C for 2 h, and finally cooled to room temperature. After cooling, it was taken out and collected and sealed in a transparent plastic bag to prevent moisture absorption, thereby obtaining corn straw biochar (CSBC).
[0071] (2) 3 g of the corn straw biochar prepared in step 1) was added to 200 mL of 2 mol / L NaOH solution to obtain a mixed solution 1. Then, the mixed solution 1 was heated at 300 r min -1 After stirring for 2 hours, the solid particles in the mixed solution 1 were filtered out and washed with deionized water for several times to remove impurities until the pH value was 7±0.5. The obtained solid particles were then dried in a drying oven at a vacuum drying temperature of 80°C and a drying time of 17 hours to obtain alkaline corn straw biochar (alkaline CSBC).
[0072] (3) Dissolve 1.5 g of carboxymethyl-β-cyclodextrin (CM-β-CD) in 75 mL of deionized water at 55-90°C, then add 2.36 g of FeCl3·6H2O and 1.62 g of FeSO4·7H2O. 3+ with Fe 2+ The molar ratio was 3:2, and a mixed solution 2 was obtained. Then, 15 mL of NH3·H2O was quickly added to the mixed solution 2 to obtain a mixed solution 3, in which the volume ratio of ammonia water to deionized water was 1:5; the mixed solution 3 was continuously stirred at room temperature at a stirring rate of 1200 r min -1, stirring time is between 2h; then the mixed solution 3 is heated to 75℃, and then 2g of alkaline CSBC prepared in step (2) is added, the mass ratio of CM-β-CD and alkaline RSBC is 0.75, and a mixed solution 4 is obtained; then 10mL of NH3·H2O is quickly added to the mixed solution 4 to obtain a mixed solution 4, the mixed solution 4 is reacted at 75℃ for 25min, and then 1.2g of sodium dodecylbenzene sulfonate (SDBS) is added to the mixed solution 4 to obtain a mixed solution 5, which is continuously stirred at 75℃; after the reaction is completed, the mixed solution 5 is aged for 0.5h, and the solid particles obtained after filtration are washed with anhydrous ethanol and deionized water for multiple times, and then dried at a constant temperature, and the vacuum drying temperature is between 80℃; the drying time is between 17h to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@CSMBC).
[0073] Embodiment 11:
[0074] A method for preparing a CM-β-CD@CSMBC adsorption material comprises the following steps:
[0075] (1) The corn straw was washed three times with deionized water to remove dust and impurities, and then dried in an oven at 60°C. It was crushed with a wall breaker and passed through a 100-mesh sieve. A certain amount of rice straw biochar was placed in a crucible, compacted, wrapped with tin foil, and placed in a muffle furnace. It was calcined at a heating rate of 10°C / min and a pyrolysis temperature of 600°C for 4 h, and finally cooled to room temperature. After cooling, it was taken out and collected and sealed in a transparent plastic bag to prevent moisture absorption, thereby obtaining corn straw biochar (CSBC).
[0076] (2) Add 2 g of the corn straw biochar prepared in step 1) into 200 mL of 2 mol / L NaOH solution to obtain a mixed solution 1. Then, the mixed solution 1 was heated at 300 r min. -1 After stirring for 2 hours, the solid particles in the mixed solution 1 were filtered out and washed with deionized water for several times to remove impurities until the pH value was 7±0.5. The obtained solid particles were then dried in a drying oven at a vacuum drying temperature of 80°C and a drying time of 17 hours to obtain alkaline corn straw biochar (alkaline CSBC).
[0077] (3) Dissolve 2 g of carboxymethyl-β-cyclodextrin (CM-β-CD) in 75 mL of deionized water at 55-90°C, then add 2.36 g of FeCl3·6H2O and 1.62 g of FeSO4·7H2O. 3+ with Fe 2+The molar ratio was 3:2, and a mixed solution 2 was obtained. Then, 15 mL of NH3·H2O was quickly added to the mixed solution 2 to obtain a mixed solution 3, in which the volume ratio of ammonia water to deionized water was 1:5; the mixed solution 3 was continuously stirred at room temperature at a stirring rate of 1200 r min -1 , stirring time is between 2h; then the mixed solution 3 is heated to 75℃, and then 2g of alkaline CSBC prepared in step (2) is added, the mass ratio of CM-β-CD and alkaline RSBC is 1, and a mixed solution 4 is obtained; then 10mL of NH3·H2O is quickly added to the mixed solution 4 to obtain a mixed solution 4, the mixed solution 4 is reacted at 75℃ for 25min, and then 1.2g of sodium dodecylbenzene sulfonate (SDBS) is added to the mixed solution 4 to obtain a mixed solution 5, which is continuously stirred at 75℃; after the reaction is completed, the mixed solution 5 is aged for 0.5h, and the solid particles obtained after filtration are washed with anhydrous ethanol and deionized water for multiple times, and then dried at a constant temperature, and the vacuum drying temperature is between 80℃; the drying time is between 17h to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@CSMBC).
[0078] Embodiment 12:
[0079] A method for preparing a CM-β-CD@CSMBC adsorption material comprises the following steps:
[0080] (1) The corn straw was washed three times with deionized water to remove dust and impurities, and then dried in an oven at 60°C. It was crushed with a wall breaker and passed through a 100-mesh sieve. A certain amount of rice straw biochar was placed in a crucible, compacted, wrapped with tin foil, and placed in a muffle furnace. It was calcined at a heating rate of 10°C / min and a pyrolysis temperature of 600°C for 2 h, and finally cooled to room temperature. After cooling, it was taken out and collected and sealed in a transparent plastic bag to prevent moisture absorption, thereby obtaining corn straw biochar (CSBC).
[0081] (2) Add 2 g of the corn straw biochar prepared in step 1) into 200 mL of 2 mol / L NaOH solution to obtain a mixed solution 1. Then, the mixed solution 1 was heated at 300 r min. -1 After stirring for 2 hours, the solid particles in the mixed solution 1 were filtered out and washed with deionized water for several times to remove impurities until the pH value was 7±0.5. The obtained solid particles were then dried in a drying oven at a vacuum drying temperature of 80°C and a drying time of 17 hours to obtain alkaline corn straw biochar (alkaline CSBC).
[0082] (3) Dissolve 1.5 g of carboxymethyl-β-cyclodextrin (CM-β-CD) in 75 mL of deionized water at 55-90°C, then add 3.15 g of FeCl3·6H2O and 1.62 g of FeSO4·7H2O. 3+ with Fe 2+ The molar ratio was between 2:1, and a mixed solution 2 was obtained. Then, 15 mL of NH3·H2O was quickly added to the mixed solution 2 to obtain a mixed solution 3, in which the volume ratio of ammonia water to deionized water was between 1:5; the mixed solution 3 was continuously stirred at room temperature at a stirring rate of 1200 r min -1 , stirring time is between 2h; then the mixed solution 3 is heated to 75℃, and then 2g of alkaline CSBC prepared in step (2) is added, the mass ratio of CM-β-CD and alkaline RSBC is 0.75, and a mixed solution 4 is obtained; then 10mL of NH3·H2O is quickly added to the mixed solution 4 to obtain a mixed solution 4, the mixed solution 4 is reacted at 75℃ for 25min, and then 1.2g of sodium dodecylbenzene sulfonate (SDBS) is added to the mixed solution 4 to obtain a mixed solution 5, which is continuously stirred at 75℃; after the reaction is completed, the mixed solution 5 is aged for 0.5h, and the solid particles obtained after filtration are washed with anhydrous ethanol and deionized water for multiple times, and then dried at a constant temperature, and the vacuum drying temperature is between 80℃; the drying time is between 17h to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar (CM-β-CD@CSMBC).
[0083] The above description is only a simpler and better embodiment of the present invention and is not intended to limit the present invention. Any modification, replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a CM-β-CD@RHMBC adsorption material, characterized in that The following steps are involved: (1) Preparation of biochar - RHBC: The biomass is washed, dried, crushed and then sieved; the sieved powder is calcined at high temperature, cooled and collected to obtain biochar - RHBC; (2) Preparation of alkaline biochar - alkaline RHBC: adding the biochar prepared in step (1) to an alkaline solution to obtain a mixed solution 1; filtering out solid particles in the mixed solution 1 after stirring, washing with water to remove impurities, and then drying the obtained solid particles to obtain alkaline biochar - alkaline RHBC, and the remaining alkaline solution is recycled. (3) Preparation of carboxymethyl-β-cyclodextrin modified magnetic biochar - CM-β-CD@RHMBC: Add the alkaline RHBC prepared in step (2) to the carboxymethyl-β-cyclodextrin solution to obtain a mixed solution 2; add FeCl3·6H2O and FeSO4·7H2O after mixing to obtain a mixed solution 3; heat the mixed solution 3 while stirring, and then add NH3·H2O to the mixed solution 3 to obtain a mixed solution 4; after the reaction, add a surfactant to the mixed solution 4 to obtain a mixed solution 5, stir the reaction, age the mixture after the reaction, filter the mixture, wash the solid particles with anhydrous ethanol and deionized water, and dry the mixture to obtain carboxymethyl-β-cyclodextrin modified magnetic biochar - CM-β-CD@RHMBC.
2. The preparation method according to claim 1, characterized in that: Step (1) the biomass is dried at 50-80° C. for 5-24 hours, crushed and sieved through a 60-150 mesh sieve; during calcination, the pyrolysis rate is between 5-15° C. / min, the pyrolysis temperature is between 300-900° C., and the pyrolysis time is between 1-7 hours.
3. The preparation method according to claim 1, characterized in that: Step (2) Mix OH in solution 1 - The concentration is between 1 and 4 mol / L, and the mass of biochar is between 1 and 200 g / L.
4. The preparation method according to claim 1, characterized in that: Step (2) The stirring rate of the mixed solution 1 is between 200 and 1200 r / min -1 , the stirring time is between 1 and 24 hours.
5. The preparation method according to claim 1, characterized in that: Step (3) adding CM-β-CD and alkaline RHBC to deionized water to obtain a mixed solution 2, wherein the mass ratio of CM-β-CD to alkaline RHBC is 0.5 to 7; Fe 3+ with Fe 2+ The molar ratio is between 1:2 and 2:
1.
6. The preparation method according to claim 1, characterized in that: Step (3) Mixing solution 2 is stirred at room temperature at a stirring rate of 800 to 1200 r / min -1 , the stirring time is between 1 and 24 hours; the mixed solution 2 is heated to 55-90°C, FeCl3·6H2O and FeSO4·7H2O are added to obtain a mixed solution 3.
7. The preparation method according to claim 1, characterized in that: Step (3) The volume ratio of ammonia water to deionized water in the mixed solution 4 is between 1:2 and 1:7, and the solution temperature is maintained at 55 to 90° C. for 25 min; the concentration of the surfactant added to the mixed solution 4 is between 1 and 30 g / L, and the stirring temperature is 55 to 90° C.
8. The preparation method according to claim 1, characterized in that: The aging time in step (3) is between 5 and 60 minutes; the obtained solid particles are washed alternately with anhydrous ethanol and deionized water for 1 to 10 times.
9. A magnetic material capable of targeted capture of valuable metal ions prepared by any one of the methods of claims 1-8.
10. Use of the CM-β-CD@RHMBC adsorption material prepared by the preparation method according to any one of claims 1 to 8 in adsorbing and removing rare earth ions in aqueous solution.
Citation Information
Patent Citations
Modified magnetic biochar adsorption material as well as preparation method and application thereof
CN118663238A
Application of recoverable magnetic tea residue biochar in aflatoxin adsorption
CN118847040A